Community Resilience to Natural Disasters in the Informal Settlements in Mwanza City, Tanzania - Hambati, Herbert (Tanzania Journal for Population studies and Development, 2015)
The impacts of natural disasters on communities living in hazard-prone areas are wide-ranging and complex, especially in Mwanza city where the landscape is characterized by highly dissected steep slopes, rock hills, narrow interfluves and river valleys in which the very poor in society mostly inhabit. The communities in such areas are prone to landslides, floods and storms that are triggered by weather and climatic changes over time and space. Over time communities in Mwanza city have accumulated traditional coping mechanisms for disaster risks and impact reduction. This paper explores local communities’ understanding of causes and impacts of hazards and disasters using their own culture, and hence their capacity to recover. It is hypothesized that peoples’ capacity to cope with nature-based disasters should hinge on a nuanced understanding of resilience of their socio-economic and ecological systems framework. The traditional technologies employed as pre- and post-disaster risk reduction measures are a reflection of a solid base for integrating with contemporary technologies in promoting resilience. In the long-term, combating poverty at individual, household, community and national levels will be crucial for enhancing resilience to hazards and disasters. A challenge to natural disaster risks reduction is how to initiate a research agenda on sustainable development policies and action plans that are disaster-risks-inclusive, with a focus on increased public awareness and enhancing resilience. Efforts to promote traditional technologies should, therefore, be directed to a school system where a new generation of academicians with access to modern-day knowledge may have an opportunity to integrate the two technologies for disaster risk reduction in various communities.